CRISPR-Cas9 for the genome engineering of cyanobacteria and succinate production - Li, Hung; Shen, Claire R.; Huang, Chun-Hung; Sung, Li-Yu; Wu, Meng-Ying; Hu, Yu-Chen (Metabolic engineering, 2016)
Cyanobacteria hold promise as a cell factory for producing biofuels and bio-derived chemicals, but genome engineering of cyanobacteria such as Synechococcus elongatus PCC 7942 poses challenges because of their oligoploidy nature and long-term instability of the introduced gene. CRISPR-Cas9 is a newly developed RNA-guided genome editing system, yet its application for cyanobacteria engineering has yet to be reported. Here we demonstrated that CRISPR-Cas9 system can effectively trigger programmable double strand break (DSB) at the chromosome of PCC 7942 and provoke cell death. With the co-transformation of template plasmid harboring the gene cassette and flanking homology arms, CRISPR-Cas9-mediated DSB enabled precise gene integration, ameliorated the homologous recombination efficiency and allowed the use of lower amount of template DNA and shorter homology arms. The CRISPR-Cas9-induced cell death imposed selective pressure and enhanced the chance of concomitant integration of gene cassettes into all chromosomes of PCC 7942, hence accelerating the process of obtaining homogeneous and stable recombinant strains. We further explored the feasibility of engineering cyanobacteria by CRISPR-Cas9-assisted simultaneous glgc knock-out and gltA/ppc knock-in, which improved the succinate titer to 435.0±35.0μg/L, an ≈11-fold increase when compared with that of the wild-type cells. These data altogether justify the use of CRISPR-Cas9 for genome engineering and manipulation of metabolic pathways in cyanobacteria. •CRISPR-Cas9 triggers programmable double strand break (DSB) and death in cyanobacteria PCC 7942.•CRISPR-Cas9-mediated DSB enables precise gene integration in PCC 7942.•CRISPR-Cas9-induced DSB improves homologous recombination efficiency.•CRISPR-Cas9 accelerates the process of obtaining homogenous recombinant strain.•CRISPR-Cas9 enables metabolic engineering of PCC 7942 for succinate production.